Development of an HPLC-UV Method for the Analysis of Drugs Used for Combined Hypertension Therapy in Pharmaceutical Preparations and Human Plasma - Serife Evrim Kepekci Tekkeli (Journal of Analytical Methods in Chemistry)
A simple, rapid, and selective HPLC-UV method was developed for the determination of antihypertensive drug substances: amlodipine besilat (AML), olmesartan medoxomil (OLM), valsartan (VAL), and hydrochlorothiazide (HCT) in pharmaceuticals and plasma. These substances are mostly used as combinations. The combinations are found in various forms, especially in current pharmaceuticals as threesome components: OLM, AML, and HCT (combination I) and AML, VAL, and HCT (combination II). The separation was achieved by using an RP-CN column, and acetonitrile-methanol-10 mmol orthophosphoric acid pH 2.5 (7 : 13 : 80, v/v/v) was used as a mobile phase; the detector wavelength was set at 235 nm. The linear ranges were found as 0.1–18.5 μg/mL, 0.4–25.6 μg/mL, 0.3–15.5 μg/mL, and 0.3–22 μg/mL for AML, OLM, VAL, and HCT, respectively. In order to check the selectivity of the method for pharmaceutical preparations, forced degradation studies were carried out. According to the validation studies, the developed method was found to be reproducible and accurate as shown by RSD ≤6.1%, 5.7%, 6.9%, and 4.6% and relative mean error (RME) ≤10.6%, 5.8%, 6.5%, and 6.8% for AML, OLM, VAL, and HCT, respectively. Consequently, the method was applied to the analysis of tablets and plasma of the patients using drugs including those substances.